Goianidade em canto: ideologia e educação no movimento da mercadoria ou na modernização do sertão goiano - Magalhães, Alcio Crisóstomo (2015)
The thesis "Goianidade in singing: ideology and education in the movement of goods or in the modernization of Goiás hinterland" is the expository synthesis of an investigative journey that anchoring in the line of research Education, Labor and Social Movements, the Graduate Program the Faculty of Education of the Federal University of Goiás, takes as a problem the question of how the project civilization goianidade produces explanatory mediations of 'collective will' that the particularity of modernization in Goiás produced as a cultural system or goiana identity. In this sense, it corresponds to a literature review in the light of materialist dialectics, of the determinants which link a set of Goiás cultural organizations, as well as their organic intellectuals, the victorious productive matrix in Brazil. The same that had historical bloc in the range of just over half a century that separates the early 1930s and the first half of the 1980's radical critique of the movement that founded the city of Goiania and it articulates the judiciary, the Holy House, the Historical and Geographical Institute, the education system, the Goiana Academy of Letters, the mass communication system (newspaper, magazine, radio and television), associations and / or employer associations (Federation of Industries, the Trade and Agriculture), the Archdiocese, the first two universities and the military allows this theory. In other words, taking as methodological theoretical support categories work, class, culture, ideology, organic intellectuals, position war, war of movement and invented tradition, it can be said that the case Goiás in their educational collusion, just shows the limits of a reality that is produced and reproduces as a commodity, so, enchanted by the ideological reversal.